THE EFFECT OF BARANGAN BANANA (Musa sapientum L.) PEEL WASTE ON TOMATO (Lycopersicum esculentum MILL.) PLANT GROWTH - Fajriana, Nurul (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2021)
Research on